2012
DOI: 10.1159/000339669
|View full text |Cite
|
Sign up to set email alerts
|

Blood Concentrations of Homocysteine and Methylmalonic Acid among Demented and Non-Demented Swedish Elderly with and without Home Care Services and Vitamin B12 Prescriptions

Abstract: Background and Aims: Total plasma homocysteine (tHcy) has been suggested as a risk factor of dementia. Our aim was to investigate potential differences in tHcy status in relation to the prescription of vitamin B12 and dementia diagnosis. We examined whether vitamin B12 prescriptions, a family history of dementia, or the need for home care service might be associated with tHcy values. Methods: A cross-sectional monocenter study comprising 926 consecutive subjects attending our Memory Care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…26 The metabolism of methyl-melonyl acid (MMA) and homocystine involves cobolamin leads to raised level of these biomarkers in vitamin B12 deficient population. 27 In our study, the homocysteine and MMA level was not studied but this is an space of increasing interest presently. The literature reported the association between raised homocystine level and hypothyroidism that improves by making the patient as euthyroid case.…”
Section: Discussionmentioning
confidence: 99%
“…26 The metabolism of methyl-melonyl acid (MMA) and homocystine involves cobolamin leads to raised level of these biomarkers in vitamin B12 deficient population. 27 In our study, the homocysteine and MMA level was not studied but this is an space of increasing interest presently. The literature reported the association between raised homocystine level and hypothyroidism that improves by making the patient as euthyroid case.…”
Section: Discussionmentioning
confidence: 99%
“…Increased dependency on the caregiver Regular monitoring of nutritional status Timely identification of malnutrition risk and regular monitoring Identification and measurement of nutritional status/risk (Annweiler et al, 2012;Bourdel-Marchasson et al, 2001;Buell et al, 2010;Burns et al, 1989;Chi et al, 2015;De Bruin et al, 2010;De Rouvray et al, 2014;Droogsma et al, 2013;Faxen Irving et al, 2009;Ferrario et al, 1996;Guerin et al, 2009;Guyonnet et al, 1998;Hagnelius, Wahlund, Schneede, & Nilsson, 2012;Ikeda et al, 2002;Keene & Hope, 1998;Kwan et al, 2005;Lyngroth et al, 2015;Milward et al, 1999;Presse et al, 2008;Rivière et al, 1998;Rivière et al, 2002;Salva et al, 2011;Scarmeas et al, 2009;Shatenstein, Kergoat, & Nadon, 2001;Shatenstein et al, 2007Shatenstein et al, , 2008Silva et al, 2013;Soto et al, 2012;Suominen et al, 2015;Tully et al, 2003;Vellas et al, 2005;Venci et al, 2015;Winograd et al, 1991) Nutritional status is a risk factor for institutional placement to use. The studies also suggested that nutritional status should be monitored regularly thereafter (Guerin et al, 2005;Isaia et al, 2011;…”
Section: Caregiver Gendermentioning
confidence: 99%